Comparative analysis of Diospyros (Ebenaceae) plastomes: Insights into genomic features, mutational hotspots, and adaptive evolution - Yue Huang; Qing Ma; Jing Sun; Li‐Na Zhou; Chan‐Juan Lai; Pan Li; Xin‐Jie Jin; Yong‐Hua Zhang (Ecology and Evolution)
Abstract Diospyros (Ebenaceae) is a widely distributed genus of trees and shrubs from pantropical to temperate regions, with numerous species valued for their fruits (persimmons), timber, and medicinal values. However, information regarding their plastomes and chloroplast evolution is scarce. The present study performed comparative genomic and evolutionary analyses on plastomes of 45 accepted Diospyros species, including three newly sequenced ones. Our study showed a highly conserved genomic structure across the Diospyros species, with 135–136 encoding genes, including 89 protein‐coding genes, 1–2 pseudogenes (Ψycf1 for all, Ψrps19 for a few), 37 tRNA genes and 8 rRNA genes. Comparative analysis of Diospyros identified three intergenic regions (ccsA‐ndhD, rps16‐psbK and petA‐psbJ) and five genes (rpl33, rpl22, petL, psaC and rps15) as the mutational hotspots in these species. Phylogenomic analysis identified the phylogenetic position of three newly sequenced ones and well supported a monophylogenetic (sub)temperate taxa and four clades in the pantropical taxa. The analysis codon usage identified 30 codons with relative synonymous codon usage (RSCU) values >1 and 29 codons ending with A and U bases. A total of three codons (UUA, GCU, and AGA) with highest RSCU values were identified as the optimal codons. Effective number of codons (ENC)‐plot indicated the significant role of mutational pressure in shaping codon usage, while most protein‐coding genes in Diospyros experienced relaxed purifying selection (dN/dS < 1). Additionally, the psbH gene showed positive selection (dN/dS > 1) in the (sub)temperate species. Thus, the results provide a meaningful foundation for further elaborating Diospyros's genetic architecture and taxonomy, enriching genetic diversity and conserving genetic resources.